SiMFlex Micromanipulation Cell with Modular Structure - Simona Noveanu; Ioan Alexandru Ivan; Dan Cristian Noveanu; Calin Rusu; Daniel Lates (Applied Sciences, 2020)
During recent years, there has been a trend towards the miniaturization of the products and of the tools necessary in the industrial processes, including those for micromanipulation. For micromanipulation, the best devices are microgrippers built such as the compliant mechanisms. In this paper, a modular structure for a micromanipulation cell is proposed. The cell has three main modules: a base platform for the working area, a micro-positioning system, and a micromanipulation system. Each module has different design variants which can be combined for specific applications, the FE (finite elements). The analysis and experimental results validate the prototype proposed for this study. In the end, an application of the SiMFlex manipulation cell for an optical microscope is proposed.